LNG Operational and Navigational Risk: An Integrated Risk Assessment for a Resilient LNG Terminal - Tomaso Vairo; Dario Cangelosi; Alessandro Manfredi; Margherita Pettinato; Bruno Fabiano (Chemical Engineering Transactions)
Liquefied Natural Gas (LNG) terminals present a complex risk environment due to the inherent hazards associated with LNG handling and the navigational challenges within port areas. A comprehensive risk assessment (RA) framework for LNG terminals, encompassing both LNG operational and navigational risks in the terminal area is presented. Key factors such as LNG transfer operations, storage conditions, and vessel traffic patterns are systematically analysed. The framework incorporates navigational risk elements, including collision, grounding, and environmental conditions, to provide an all-embracing risk profile. Through extensive case studies and scenario analyses, the RA framework demonstrates its efficacy in identifying critical risk contributors and assessing mitigation measures. The results highlight the importance of a dual-focus approach in risk management, considering interdependencies between the components of the sociotechnical infrastructure and systems, e.g. in port areas, combining operational safety protocols for LNG handling with robust navigational safety strategies. The integrated assessment can support informed decision-making and enhance the overall safety and reliability of LNG terminal operations, ultimately contributing to a safer and more resilient energy transport infrastructure and port environment.